ТҮҮХЭН ЭКОЛОГИ: УУР АМЬСГАЛЫН ӨӨРЧЛӨЛТ ТҮҮХЭН ҮЙЛ ЯВЦАД НӨЛӨӨЛӨХ НЬ - У.ЭРДЭНЭТУЯА (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2002)
In keeping with the theme "Influence of climate change on historical events", have involved some key concepts on Ecological anthropology and Human ecology, belonging ethnoecology, historical ecology, formulated by researchers, and have compiled some examples of influences of Climate change on to evolutionary development of human species, historical events, prosperity and descent of human societies.